Information Processing in Computer-Assisted Interventions Third International Conference, IPCAI 2012, Pisa, Italy, June 27, 2012. Proceedings - Abolmaesumi, Purang; Joskowicz, Leo.; Navab, Nassir; Jannin, Pierre; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proceedings of the Third International Conference on Information Processing in Computer-Assisted Interventions IPCAI 2012, held in Pisa, Italy, on June 27, 2012. The 17 papers presented were carefully reviewed and selected from 31 submissions during two rounds of reviewing and improvement. The papers present novel technical concepts, clinical needs and applications as well as hardware, software and systems and their validation. The main technological focus is on patient-specific modeling and its use in interventions, image-guided and robotic surgery, real-time tracking and imaging.
Keywords: Computer science; Radiology, Medical; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; User Interfaces and Human Computer Interaction; Image Processing and Computer Vision; Computer Graphics; Pattern Recognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Imaging / Radiology